Surface Temperature Variations Due to Land Cover Changes in Jambi City: A Comparative Study of 2013 and 2024: Variasi Suhu Permukaan Akibat Perubahan Tutupan Lahan di Kota Jambi: Studi Perbandingan Tahun 2013 dan 2024 - Simarmata, Agustina Rida; Achmad, Eva; Harmes; Purnama, Edwine (JURNAL HUTAN TROPIKA, 2025)
This study investigates the spatio-temporal changes in land surface temperature (LST) patterns in Jambi  City, Indonesia, between 2013 and 2024 using Landsat 8-9 OLI/TIRS imagery. The research employs thermal band analysis (bands 10 and 11) and geographical information systems to evaluate urban heat  island (UHI) effects across 68 sub-districts. Results demonstrate significant thermal    landscapetransformations, with surface temperatures expanding from 21.5-26.20°C in 2013 to 19.02-27.33°C  in 2024. Highly urbanized areas, particularly in Jambi Selatan, Jelutung, and Paal Merah districts, experienced the most substantial temperature increases (up to 1.13°C), while areas maintaining vegetation cover and proximity to water bodies showed remarkable thermal stability. The study reveals strong correlations between land use changes and temperature variations, with built-up areas exhibiting significantly higher temperatures compared to vegetated regions and water bodies. These findings provide crucial insights for urban planning and climate adaptation strategies, emphasizing the importance of preserving green spaces and water bodies as natural cooling mechanisms in rapidly developing tropical cities.